The diesel engine - Hilgers, Michael (Springer Vieweg, 2021)
The aim of this work, consisting of 9 individual, self-contained booklets, is to describe commercial vehicle technology in a way that is clear, concise and illustrative. Compact and easy to understand, it provides an overview of the technology that goes into modern commercial vehicles. Starting from the customer's fundamental requirements, the characteristics and systems that define the design of the vehicles are presented knowledgeably in a series of articles, each of which can be read and studied on their own. This volume, The Diesel Engine, provides an initial overview of the vast topic that is the diesel engine. It offers basic information about the mechanical functioning of the engine. The integration of the engine in the vehicle and major systems such as the cooling system, the fuel system and the exhaust gas treatment system are explained so that readers in training and in a practical setting may gain an understanding of the diesel engine. Content Diesel fuel and air.- The mechanics of the engine.- Integrating the engine in the vehicle.- The fuel system and fuel injection.- The exhaust system.- Thermodynamics.- Abbreviations and symbols. The target groups Participants in master classes and those studying individual aspects of commercial vehicle technology Professors and lecturers instructing in the field of commercial vehicle technology Consultants and experts who need background knowledge and technical expertise regarding commercial vehicle technology Personnel working in the commercial vehicle technology or supply industry who are assigned to a new work area Cost planners and logistics companies The Authors Dr. Michael Hilgers is currently director of the testing center at BFDA, a Foton Daimler truck joint venture in China. Before that he was head of different development departments in Commercial Vehicle Development at Mercedes-Benz Trucks. Dr. Wilfried Achenbach has worked in the automotive industry for over 30 years. Recently he retired as Head of Development at Daimler Trucks North America.